International Student Handbook - Martirosyan, Nara M. (Journal of International Students, 2016)
For the past 15 years, the number of international students in American higher education has increased steadily (Institute of International Education, 2014). According to the Institute of International Education (2014), "The United States hosts more of the world’s 4.5 million globally mobile college and university students than any other country in the world" (para. 1). The 29th edition of International Student Handbook published by the College Board (2015) is the most recent guide for prospective international students interested in postsecondary education in the United States.